Homicide : towards a deeper understanding - Skott, Sara (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Homicide: Towards a Deeper Understanding offers an in-depth analysis into the phenomenon of homicide, examining different types of homicide and how these types have changed over time. Based on original analysis on Scottish data, this book draws upon an international body of research to contextualize the findings in a global setting, filling an important gap in the homicide literature pertaining to the relationship between trends in homicide and violence. Examining homicide from gendered as well as Gothic perspectives, this book also relates homicide to novel, critical theory. The book covers a thorough description of different types of homicide, including sexual homicide, and provides an explorative approach to the identification of homicide subtypes. The book also explores how these findings relate to current homicide theory, and proposes a new theoretical framework to gain a deeper understanding of this crime. The main argument of the book is that if homicide and its relationship to wider violence is to be fully understood, theoretically as well as empirically, this crime needs to be disaggregated in a way that reflects the underlying data. Overall, this book therefore fills an important gap in criminological literature, providing an in-depth understanding of one of the most serious violent crimes"--
OCLC-licensed vendor bibliographic record.
Keywords: Homicide; PSYCHOLOGY / Social Psychology; SOCIAL SCIENCE / Criminology; SOCIAL SCIENCE / Violence in Society